Cracking performance of rubberized RAP mixtures with Sasobit. (14th February 2022) - Abdollahi, Seyed Farhad; Karimi, Mohammad M.; Jahanbakhsh, Hamid; Tabatabaee, Nader
Highlights: SCB tests carried out at −20 °C and 25 °C to assess the cracking performance. Overall assessment was used with regard to sustainability and mixture performance. Combined use of Sasobit and CR in RAP mixtures improved overall performance. Deficient amount of binder prevented the CR to effectively improve the cracking performance. Abstract: Incorporation of reclaimed asphalt pavement (RAP) and crumb rubber (CR) materials into asphalt mixtures have been of great importance from sustainability point of view. Although, inclusion of RAP materials in asphalt mixtures improves the rutting resistance at high temperature, the low temperature (LT) and intermediate temperature (IT) cracking performance of RAP mixtures may need additional considerations. In this regard, different schemes of modification have been applied to RAP mixtures to address its performance weaknesses. This study evaluated the effect of RAP and CR in combination with Sasobit and hydrated lime on the cracking performance of asphalt mixtures. The LT and IT semi-circular bending (SCB) tests showed that up to 15% CR modification improved the cracking resistance. However, at 18% CR fatigue performance of the RAP mixture slightly declined. This is attributed to the insufficient binder content in the asphalt mixture leading to the reduced fatigue performance of the mixture. The results also emphasized the use of WMA additive, as workability promoter, for improving the IT cracking performance of rubberized RAP mixtures. Finally, an overall assessment approach was utilized to select the asphalt mixture with best overall performance while upholding the sustainability considerations. In this regard, the combined application of Sasobit and CR modification to the RAP mixtures resulted in an overall better performance compared to that of the control mixture.